2015
DOI: 10.3892/or.2015.4411
|View full text |Cite
|
Sign up to set email alerts
|

miR-340 suppresses cell migration and invasion by targeting MYO10 in breast cancer

Abstract: Breast cancer is one of the most common malignant tumors among females, and can seriously affect the physical and mental health and even threaten the lives of women. Recently, research has demonstrated that microRNAs (miRNAs), as a new method of regulation, have been shown to have oncogenic and tumor‑suppressive functions in human breast cancer. Detection of their expression may lead to the identification of novel markers for breast cancer. In the present study, we firstly detected miR‑340 expression and found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Interestingly, making use of miRNA expression analysis and RT-PCR, we also found that level of miR-340 was significantly reduced in ovarian cancer cells compared to relevant normal cells [28]. In addition, several reports have demonstrated that miR-340 was also evidently down-regulated in colorectal cancer, breast cancer, glioblastoma and oral squamous cell carcinoma [29][30][31][32]. Therefore, aberrant regulation of miR-340 was altofrequent of in multiple types of cancer cells and tissues, indicating that decreased miR-340 might play a critical role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, making use of miRNA expression analysis and RT-PCR, we also found that level of miR-340 was significantly reduced in ovarian cancer cells compared to relevant normal cells [28]. In addition, several reports have demonstrated that miR-340 was also evidently down-regulated in colorectal cancer, breast cancer, glioblastoma and oral squamous cell carcinoma [29][30][31][32]. Therefore, aberrant regulation of miR-340 was altofrequent of in multiple types of cancer cells and tissues, indicating that decreased miR-340 might play a critical role in tumorigenesis.…”
Section: Discussionmentioning
confidence: 70%
“…Examination of the expression status, biological function and underlying mechanisms of specific miRNAs in gastric cancer can contribute to the identification of novel biomarkers and therapeutic targets in human gastric cancer. Previous studies have shown that miR-340 plays an important role in human cancers (8)(9)(10)(11)(12)(13)(14). It was found to inhibit the metastatic behavior of breast cancer cells (14) while it decreased the proliferation and promoted the cell apoptosis of prostate cancer cells (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-340 (miR-340) has been found to play a critical role in human cancers, including breast (8,9), prostate (10,11), and esophageal cancer (12), hepatocellular carcinoma (13) and glioma (14). Functionally, miR-340 was found to inhibit the migration and invasion of breast cancer cells by inhibiting the Wnt pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…As the actin bundling protein fascin is also overexpressed in prostate cancer [103], we speculated that when MYO10 is knocked down in PC-3 cells, fascin mislocalises and bundles actin filaments in the cell body. Overexpression levels of MYO10 have been linked to a reduction in levels of miR-340 [104] and to an interaction with mutant p53 [99] in breast cancer. However, we did not find a link between mutant p53 and MYO10 in prostate cancer cells [5].…”
Section: Class 5 6 10 and 19 Myosin Isoformsmentioning
confidence: 99%